2013
DOI: 10.1017/s0031182013000760
|View full text |Cite
|
Sign up to set email alerts
|

Does the carotenoid-based colouration ofPolymorphus minutusfacilitate its trophic transmission to definitive hosts?

Abstract: Freshwater gammarids infected with the acanthocephalan parasite Polymorphus minutus show behavioural alterations but also differ from uninfected individuals in their appearance because of the carotenoid-based colouration of the parasite visible through the cuticle. However, it's not clear whether this phenotypic alteration is an adaptation favouring parasite transmission to the definitive host. To test this hypothesis, we investigated the selective preference of mallard towards two prey types: uninfected gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Moreover, due to the structural properties of iridovirus causing iridescence (Williams 2008), infected D. magna showed a higher reflectance in the UV and visible domains than apparently healthy D. magna. Infected D. magna may thus become more visible (especially considering the larger size of infected individuals) and then more attractive (O'Keefe et al 1998, Modarressie et al 2013, Jacquin et al 2013) for Notonecta sp., which has a high visibility in UV (375 nm) and green (520 nm) (Bennett and Ruck 1970). This is consistent with the tendency observed here in which Notonecta sp.…”
Section: Reduction Of Survival But Limited Effects On Vulnerability T...mentioning
confidence: 99%
“…Moreover, due to the structural properties of iridovirus causing iridescence (Williams 2008), infected D. magna showed a higher reflectance in the UV and visible domains than apparently healthy D. magna. Infected D. magna may thus become more visible (especially considering the larger size of infected individuals) and then more attractive (O'Keefe et al 1998, Modarressie et al 2013, Jacquin et al 2013) for Notonecta sp., which has a high visibility in UV (375 nm) and green (520 nm) (Bennett and Ruck 1970). This is consistent with the tendency observed here in which Notonecta sp.…”
Section: Reduction Of Survival But Limited Effects On Vulnerability T...mentioning
confidence: 99%
“…non-white). Infected D. magna may thus become more visible (especially considering the larger size of infected individuals) and more attractive (O'Keefe et al 1998, Jacquin et al 2013, Modarressie et al 2013) for Notonecta sp., which has a high sensitivity in UV (375 nm) and green (520 nm) (Bennett and Ruck 1970). This is consistent with the observed preference of Notonecta sp.…”
Section: Reduction Of Survival But Limited Effects On Vulnerability T...mentioning
confidence: 99%
“…The altered coloration was suggested to facilitate predation by and thus transmission to final hosts (fishes and waterbirds, respectively). Indeed Bakker, Mazzi, and Zala () and Jacquin, Mori, and Médoc () showed that gammarids painted with an orange spot on the cuticle were preferentially preyed upon by three‐spined sticklebacks and mallards, clearly indicating that the altered coloration affects predation of the intermediate host. Interestingly, a subsequent study found no significant impact on predation by trout (Kaldonski et al., ) suggesting the colour effects differ among species (see also Thünken et al., unpublished data in Table S1).…”
Section: Experimental Manipulation Of Intermediate Host Traitsmentioning
confidence: 99%